The influence of education packages on adequacy of breast milk and baby weight gains during the covid-19 pandemic - Nur Elly; Demsa Simbolon; Iin Nilawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: The process of breastfeeding in the early days of a baby's life often fails due to a lack of breast milk production. Breastfeeding education is an effort that needs to be done to prevent and overcome breastfeeding failure. During the COVID-19 pandemic, education for pregnant and postpartum women is needed that can be done online. Objectives: The purpose of this study was to determine the effectiveness of the "Edu-ASI" package on the adequacy of breastfeeding and increasing infant weight in Bengkulu City. Methods:This study uses a quasi-experimental design with a post-test design with a control group. The population in this study were 3rd trimester pregnant women (with gestational age above 35 weeks who carried out ANC at BPM Bengkulu City followed by post partum on the fourteenth day. The number of samples was 15 people in the intervention group and 15 people in the control group obtained by consecutive sampling. In the intervention group, an education package was given with educational media tools through Edu_ASI in the form of 3 video parts containing the concept and how to breastfeed, then mentoring and post-test measurement of the adequacy of breastfeeding were carried out and 2 weeks after delivery the baby was weighed.In the control group only education was given by the midwife as education that is usually done by midwives. The adequacy of breast milk is measured based on indicators from the baby and the increase in baby weight by comparing the increase in birth weight with the baby's weight at the age of 2 weeks. Result: The analysis was carried out using the T test and man witney. control and case respondents. The Edu-ASI package was effective for breastfeeding adequacy with a P value of 0.007, and the Edu-ASI package was less effective in increasing the baby's weight gain which was measured 2 weeks after delivery with a p-value test of 0.671. Conclusions: The Edu-ASI package is expected to support the success of the Exclusive Breastfeeding program, especially during the COVID-19 pandemic.